Optimization of Computer Network Performance through Traffic Management and Bandwidth Allocation - Dirja Nur Ilham; Muhammad Khoiruddin Harahap; Muhammed Saat Talib; Arie Budiansyah; Rudi Arif Candra (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Computer network performance is highly dependent on effective traffic management and proper bandwidth allocation, especially in network environments with a large number of users and diverse service demands. Uneven bandwidth distribution often leads to degraded service quality, including low throughput, high delay, and increased packet loss. This study aims to analyze and optimize computer network performance through the implementation of traffic management and bandwidth allocation using the Simple Queue and Queue Tree methods on a MikroTik router. An experimental research approach was employed by comparing network performance before and after the application of bandwidth management mechanisms. The evaluation was conducted based on Quality of Service (QoS) parameters, namely throughput, delay, and packet loss, in accordance with the TIPHON standard. The experimental results indicate a significant improvement in network performance after the implementation of Simple Queue and Queue Tree. Throughput increased substantially, while delay and packet loss were considerably reduced, resulting in improved service quality categories. The Simple Queue method effectively ensured fair bandwidth distribution among users by limiting per-user bandwidth usage, whereas the Queue Tree method enhanced performance by prioritizing network traffic based on service types. The combination of these methods successfully minimized bandwidth monopolization, reduced network congestion, and improved overall network stability. Therefore, the implementation of Simple Queue and Queue Tree proves to be an effective solution for optimizing bandwidth utilization and enhancing Quality of Service in computer networks with high user density and heterogeneous traffic characteristics.